One-particle spectral function singularities in a one-dimensional gas of spin-1/2 fermions with repulsive delta-function interaction - T. Čadež (Nuclear Physics B, 2019)
The momentum, fermionic density, spin density, and interaction dependencies of the exponents that control the (k,ω)-plane singular features of the one-fermion spectral functions of a one-dimensional gas of spin-1/2 fermions with repulsive delta-function interaction both at zero and finite magnetic field are studied in detail. Our results refer to energy scales beyond the reach of the low-energy Tomonaga-Luttinger liquid and rely on the pseudofermion dynamical theory for integrable models. The one-fermion spectral weight distributions associated with the spectral functions studied in this paper may be observed in systems of spin-1/2 ultra-cold fermionic atoms in optical lattices.